The influence of digital marketing communication on consumer purchasing decisions in a pandemic (COVID-19) - Ayon, Sadman Sakib (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.